Brunnárdalur Ag-Au (Cu-Te-Bi) epithermal vein, northern Iceland - Halldór Guðmundsson 1992- (2024)
The study area of Skertlufjall was geologically mapped and samples from the 2 m wide Brunnárdalur epithermal vein were collected, studied and analyzed using petrographic microscopy, scanning electron microscopy, fluid inclusion microthermometry and Raman spectrometry. The area is on the outskirts of the Vididalur-Vatnsdalur central volcano and consists of a stratigraphically controlled bimodal lava pile that has likely been uplifted due to an intrusive body. Quartz textures within the vein are identified as mosaic, colloform, comb, feathery and ghost-bladed. Alteration minerals identified in the basalt host rock are calcite, quartz, chlorite, actinolite and garnet. Homogenization temperatures derived from fluid inclusion microthermometry for liquid-rich fluid inclusion assemblages (FIAs) are 188-206°C and from coexisting liquid-rich and vapor-rich FIA 247°C based on the lowest homogenization temperature. The salinity of the fluid is between 5.54 wt.% to 9.59 wt.% NaClequiv. The metallic enrichment of the vein is caused by the minerals electrum, hessite, native tellurium, bismuth tellurite (ehrigite or hedleyite), chalcopyrite, galena and sphalerite. A possible temperature evolution of the hydrothermal system is: Stage I, early high temperature event peaking at >300°C forming actinolite and garnet, followed by cooling of the system causing pervasive calcite alteration. Stage II, chlorite alteration during the formation of the Brunnárdalur vein where deposition of amorphous silica and chalcedony into colloform texture, gold, sulfide and tellurite minerals occurred due to boiling. The morphology of the vein shows characteristics of low sulfidation epithermal ore deposits. The high salinity compared to low sulfidation deposits could be explained by magmatic fluid contributing to a meteoric water dominated system reflected also in the presence of tellurites and native tellurium. Rannsóknarsvæðið í Skerltufjalli var jarðfræði kortlagt og sýnum úr 2 m breiðu Brunnárdals æðinni var safnað, skoðuð með ...